Integrative bulk and single-cell transcriptomic analysis reveals COL1A2-driven ECM remodeling and focal adhesion signaling associated with the transition from non-muscle-invasive to muscle-invasive bladder cancer - Li, Menglu; Liu, Xinwei; Xue, Yuhui; Lu, Yichen; Chen, Zhiqiang; Zhang, Yuwei; Chen, Weiguo; Zhao, Shan-Chao; Wang, Ke; Feng, Ninghan (Frontiers in Oncology, 2026)
BackgroundBladder cancer (BCA) shows significant prognostic differences between non-muscle-invasive (NMIBC) and muscle-invasive (MIBC) forms. While NMIBC frequently recurs and can progress to invasive disease, reliable biomarkers to monitor this transition are lacking. Extracellular matrix (ECM) remodeling is a critical factor influencing tumor aggressiveness, yet the key regulators of ECM changes across BCA stages remain unclear. In this study, we investigate the role of COL1A2 in ECM-related tumor biology and its potential as a prognostic biomarker for BCA progression.MethodsWe utilized a multi-step bioinformatics pipeline, analyzing RNA-seq data from TCGA and GEO datasets to identify molecular differences between NMIBC and MIBC. Prognostic markers were prioritized via differential expression analysis, Cox regression, and Kaplan–Meier survival analysis. The regulatory network was explored using protein-protein interaction analysis, and ECM-related activity was quantified through ssGSEA. Cell-type-specific insights were gained through single-cell RNA-seq analysis, and intercellular communication was deciphered using CellChat. Functional validation was performed through in vitro knockdown experiments in BCA cell lines.ResultsCOL1A2 emerged as a key prognostic ECM-related gene associated with MIBC. Single-cell RNA-seq analysis revealed that COL1A2 and ECM components were predominantly enriched in matrix cancer-associated fibroblasts (CAFs), with PTK2 (FAK, focal adhesion kinase) upregulated in epithelial cells undergoing epithelial-mesenchymal transition (EMT). CellChat analysis uncovered a dominant COL1A2-mediated signaling axis from matrix CAFs to EMT epithelial cells via COL1A1/2–SDC1/4 ligand-receptor interactions. Functional assays confirmed that COL1A2 knockdown significantly impaired MIBC cell invasion and migration by suppressing ECM remodeling and EMT.ConclusionOur results suggest that the COL1A2–ECM–FAK signaling axis plays a critical role in MIBC progression, and COL1A2 could serve as a potential biomarker and therapeutic target for muscle-invasive bladder cancer.